Impact of positive end expiratory pressure on left internal jugular vein size - Sharma, Mona; Shrestha, Babu Raja; Moktan, Sushila Lama; Karki, Manan (Journal of Kathmandu Medical College, 2018)
Background: Increasing the cross sectional area (CSA) of the left internal jugular vein facilitates cannulation and decreases complications. But, the literature is sparse regarding the methods to increase the cross sectional area of the left internal jugular vein. Objective: To assess the changes that occur in cross sectional area of left internal jugular vein after application of different levels of positive end expiratory pressure and compare the findings with right internal jugular vein. Methodology: Sixty-four patients were included. Antero posterior diameter, transverse diameter and cross sectional area of left and right internal jugular vein was measured using two-dimensional ultrasound before the induction of anesthesia and after intubation at positive end expiratory pressure of 0, 5, 10 and 15 cm H2O. Result: The increase in positive end expiratory pressure was associated with increase in cross sectional area, anteroposterior and transverse diameter of left internal jugular vein. At 10 cmH2 Opositive end expiratory pressure, left internal jugular vein cross sectional area increased significantly by 22.8% that is 1.34±0.53cm2(P value< 0.05). The right internal jugular vein is significantly larger than left at baseline and at all levels of studied positive end expiratory pressure. The percentage increase of cross sectional area for both internal jugular veins was similar. Conclusion: The left internal jugular vein cross sectional area increment has direct relationship with increment of positive end expiratory levels at studied points. However, above 10 cm H2O of positive end expiratory pressure, there was only non significant increase (P value > 0.05).